Sky (poem) - William Stafford (Symphony in the Flint Hills, 2014)
A poem by William Stafford calling upon the sky as a constant in his life
Keywords: poem; poetry; poet; Kansas; sky; sunrise; clouds; blue; Twilight; William Stafford